The relationship between sleep quality and smartphone use on bruxism in dental clerkship students of Faculty of Dentistry Hasanuddin University : Hubungan antara kualitas tidur dan penggunaan smartphone terhadap bruxism pada mahasiswa kepaniteraan Fakultas Kedokteran Gigi Universitas Hasanuddin - Ramadhani, Andi Ayu Dwi; Samad, Rasmidar; Anwar, Ayub Irmadani; Nursyamsi; Burhanuddin; Akbar, Fuad Husain (Makassar Dental Journal, 2025)
Background: Bruxism is related to sleep, along with increased anxiety and stress during sleep and poor sleep quality is the main reason. Smartphones have become an integral part of university students' lives, especially in academic and social activities. However, smartphone use at night can inhibit melatonin production due to blue light exposure, potentially increasing the incidence of bruxism. Objective: to determine the relationship between sleep quality and smartphone use on the incidence of bruxism in clerkship students of the Faculty of Dentistry, Hasanuddin University. Methods: This study used a cross-sectional design with a total of 103 clerkship students. Sleep quality was measured using the Pittsburgh Sleep Quality Index, Smartphone use using self-reported Questionnaire and Bruxism was measured using self-reported Questionnaire and observation of people around. Data analysis using SPSS ver. 26. Results: there is a significant relationship between sleep quality and the incidence of bruxism (p=0.041) and smartphone use on the incidence of bruxism (p=0.043). Conclusion: sleep quality and smartphone use are associated with bruxism.